Study on Decarburization Mechanism and Law of GCr15 Bearing Steel during Heat Treatment - Hui Wang; Fuyong Su; Zhi Wen (Advances in Materials Science and Engineering)
In order to understand the effects of heating temperature and holding time on decarburization of GCr15 bearing steel, an experimental device for heat treatment of bearing steel was designed and the sample was heated and held by a tubular heating furnace. The microstructure and depth of decarburized layer of bearing steel under various working conditions were observed and measured by a metallographic microscope. The results show that the total decarburization depth increases with the increase of temperature; almost no decarburization occurred below 700°C; ferrite decarburization occurred at 750°C; partial decarburization began to occur at 820°C; after 900°C, the decarburization layer is mainly partial decarburization. When the heating temperature is below 1000°C, the depth of total decarburization layer increases slowly and increases rapidly after 1000°C. The total depth of decarburization layer is directly proportional to the square root of holding time. The relationship between the depth of the total decarburization layer of bearing steel and the heating temperature and holding time in the annealing process was obtained.